Coexistence of Basic and Dependent Contracts in the Case of Cession of Debt; Comparative Study in Iranian and French Law - Pejman Mohammadi (پژوهش های حقوق تطبیقی)
The cession of debt contract, is a dependent contract which in many ways, continuous and sometimes is subordinate to the main contract. Creditor, as a party to this contract, generally consents to this when knows that this method, reduces the risk of non-fulfillment of an obligation. A question that arises is that what is the effect of voluntary transfer of contractual debt in the main contract which was the origin of the transferred debt? In Iranian law, although this matter from the main debtor versus creditor is considered as fulfillment of an obligation, it may never lead to practical receipt of credit by creditor. Despite of cession of debt, other terms and conditions of the main contract remain in effect. Sometimes, cession of debt causes the loss of some rights, Such as lien right of parties and beneficiary’s option. The principle of fulfillment of an obligation of transfer of debt is on the part of debtor against creditor. Therefore, just as fulfilling of obligation to all or some of obligations arising from the contract does not cause its dissolution, transfer of contractual obligation does not have such an effect. Nevertheless, Sometimes the voluntary transfer of contractual debt causes a change in status of parties to the contract in relation to rights and obligations and priority and delay of their implementation. Survival and dissolution of the contract as an origin of debt also affects the rights and obligations and even the survival of the debt transferor contract. In French law, cession of debt, following the laws of other European Countries especially Germany, has recently entered the civil code of that country since 2016. Despite of the acceptance of this institution, neither the cession of debt in the real sense occurs (except in exceptional cases) nor as a consequence, any of the effects of this matter can be seen in the basic contract; except in the case of stipulation of parties to the cession of debt contract. This article examines these cases with an analytical and descriptive method.